2009
DOI: 10.1176/appi.ps.60.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Police Encounters Among Persons With and Without Serious Mental Illness

Abstract: More resources should be allocated to support persons with mental illness in the community because they tend to have high rates of repeated police contacts for a variety of offenses. The findings highlight the need for gender-specific intervention programs. Administrative databases can be useful tools in examining police contacts among persons with mental illness and monitoring change after policy and program implementation for those at risk of police encounters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Upon contact, police officers have the option of handling the situation through warnings or diversion to mental health services (e.g., taking the individual to hospital), or through making an arrest under criminal law. Unfortunately, as general mental health services become increasingly difficult to access, police have fewer options when dealing with mentally disordered offenders and may have to resort to making arrests and directing these individuals to forensic mental health services (Alford, 2002;Crocker, Hartford & Heslop, 2009;Seto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Upon contact, police officers have the option of handling the situation through warnings or diversion to mental health services (e.g., taking the individual to hospital), or through making an arrest under criminal law. Unfortunately, as general mental health services become increasingly difficult to access, police have fewer options when dealing with mentally disordered offenders and may have to resort to making arrests and directing these individuals to forensic mental health services (Alford, 2002;Crocker, Hartford & Heslop, 2009;Seto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…When research has examined the role of gender among offenders with SMI, it has most often focused on violent behavior and has been largely based on hospitalized patient samples that include subjects who may be quite ill and for whom symptom risk factors may overshadow gender effects confounding study results. Recent exceptions are the studies conducted by Crocker et al 16 and Binswanger et al 8 Crocker found that among community dwelling persons without mental illness, men are significantly more likely to have criminal justice contacts, to have a greater number of offenses, to reoffend more quickly, and be charged for a suspected offense. Among community dwelling persons with mental illness, the gender difference for these measures were still significant but weaker.…”
mentioning
confidence: 99%
“…Currently, it is not known if the popular hypothesis that men and women in our society are treated differently in the criminal justice system is accurate as findings on gender, violence, offending behavior, and patterns of arrest among women and men with SMI have been inconsistent [14][15][16] . While some studies show that in the general population, males are much more likely than females to be arrested for violent behavior, among psychiatric patients, this gender difference is less clear 17,18 .…”
mentioning
confidence: 99%
“…Incarcerating persons with MI absorbs criminal justice resources, straining the system and placing people in settings that were not intended to address mental health problems. In general, prisons are failing people with MI (Committee on Psychiatry and the Community, 2009), who are more likely to recidivate, compared to people with no MI (see, e.g., Crocker, Hartford, & Heslop, 2009;Gagliardi, Lovell, Peterson, & Jemelka, 2004). MacKenzie's (2006) review of what works in corrections does not mention programming specific to individuals with MI.…”
Section: Imprisonment Of Individuals With Mental Illnessmentioning
confidence: 99%
“…Although people with MI disproportionately come into contact with the police (Crocker et al, 2009), they are also at greater risk for victimization because of the failure of police protection (Brekke, Prindle, Bae, & Long, 2001;Choe et al, 2008;Teplin et al, 2005). Hence, persons with MI are more susceptible to violence during their interactions with police, yet more likely to be victimized when the police are absent.…”
Section: Victimization Against and Procedural Justice For People Withmentioning
confidence: 99%